2021
DOI: 10.14202/vetworld.2021.1450-1458
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of codon usage bias of classical swine fever virus

Abstract: Background and Aim: Classical swine fever (CSF), caused by CSF virus (CSFV), is a highly contagious disease in pigs causing 100% mortality in susceptible adult pigs and piglets. High mortality rate in pigs causes huge economic loss to pig farmers. CSFV has a positive-sense RNA genome of 12.3 kb in length flanked by untranslated regions at 5' and 3' end. The genome codes for a large polyprotein of 3900 amino acids coding for 11 viral proteins. The 1300 codons in the polyprotein are coded by different combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…An ENC value >35 indicates a low CUB in the ASFV complete genome [ 25 ]. This finding aligns with previous studies on other porcine viruses, such as porcine circoviruses (54.71±0.87) [ 43 ], porcine parvoviruses (57.433±0.192) [ 44 ] and classical swine fever virus (52.69±0.47) [ 45 ]. The limited codon preference observed in these viruses may promote effective replication in diverse host cells [ 46 ].…”
Section: Resultssupporting
confidence: 92%
“…An ENC value >35 indicates a low CUB in the ASFV complete genome [ 25 ]. This finding aligns with previous studies on other porcine viruses, such as porcine circoviruses (54.71±0.87) [ 43 ], porcine parvoviruses (57.433±0.192) [ 44 ] and classical swine fever virus (52.69±0.47) [ 45 ]. The limited codon preference observed in these viruses may promote effective replication in diverse host cells [ 46 ].…”
Section: Resultssupporting
confidence: 92%
“…Earlier studies reported similar results in related plots [40,73,90,91]. While ENC-GC3 plot analysis is widely utilized to measure CUB, it alone is not su cient to discern the speci c contributions of mutation pressure and translational selection [65,92]. In order to delve deeper into the factors shaping codon usage patterns, neutrality plot analysis and PR2 plot analysis were conducted.…”
Section: Discussionmentioning
confidence: 72%
“…We observed that the frequencies of CG and TA dinucleotides in the IIV6 DNA ligase gene were underrepresented among the 16 dinucleotides. Dinucleotide CG is generally underrepresented in most viruses, including Hepatitis C virus, Hepatitis E virus and classical swine fever virus [92,100,101]. Moreover, the underrepresentation of CG and TA dinucleotides is considered as a strategy employed by viruses to evade reduce nonsense mutations, the host immune system and prevent cleavage by RNase [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the extent to which the bias in the codon usage pattern affects viral-host adaptiveness influences replication efficiency, virulence, protein synthesis, and virus survival. Several studies have suggested that mutational pressure is the primary driving force behind the formation of a codon use pattern [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…To estimate selection and evolutionary pressure on protein-coding areas, the proportion of the substitution rate at non-synonymous and synonymous sites is quantified. The dN/dS ratio is the most used method [9].…”
Section: Introductionmentioning
confidence: 99%